Addis Ababa, Ethiopia : Enhancing Urban Resilience - World Bank Group (World Bank, Washington, DC, 2015)
Cities are vulnerable to many types of shocks and stresses, including natural hazards like storms and sea level rise, but also man-made ones like economic transformation and rapid urbanization. These shocks and stresses have the potential to bring cities to a halt and reverse years of socio-economic development gains. Cities that are to grow and thrive in the future must take steps to address these shocks and stresses. Simply put, a resilient city is one that can adapt to these types of changing conditions and withstand shocks while still providing essential services to its residents. A resilient city can keep moving toward its long-term goals despite the challenges it meets along the way. In February 2015, a team of specialists from the World Bank Group worked with government officials, experts and stakeholders in Addis Ababa to identify the priority actions and investments that will enhance the city’s resilience to these current and future challenges. They explored options to transform planned or aspirational projects into initiatives that will also enhance the city’s resilience. As the largest city in Ethiopia and one of the fastest growing cities in Africa, Addis Ababa plays an important role in promoting the well-being of the country and economic prosperity in the region. For Addis Ababa, efforts to promote greater resilience must be closely aligned with the city’s vision to be a safe and livable city, ensure the national goal of becoming a middle-income country by 2025, and become Africa’s diplomatic capital.